2020
DOI: 10.1007/s10695-020-00827-3
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol affects the innate immune response in common carp

Abstract: Inflammation is the evolutionary conserved immune response to harmful stimuli such as pathogens or damaged cells. This multistep process acts by removing injurious stimuli and initiating the healing process. Therefore, it must be tightly regulated by cytokines, chemokines, and enzymes, as well as neuroendocrine mediators. In the present work, we studied the immunoregulatory properties of 17β-estradiol (E2) in common carp. We determined the in vitro effects of E2 on the activity/polarization of macrophages and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 77 publications
(122 reference statements)
1
8
0
1
Order By: Relevance
“…The short exposure of Common carp macrophages to a 100 µg/L BPA concentration was followed by a significant increase in Ca 2+ levels and expression of genes such as il6, il11, M17 that are related to immunotoxicity. Similar research on the effect of 17β-ethinylestradiol on juvenile Common carp was carried out by Maciuszek et al [ 116 ]. In the in vivo part of the performed studies, fish were fed with feed with the addition of E2 (20 mg/kg) and infected with Aeromonas salmonicida bacteria, for in vitro part monocyte/macrophage cell suspensions were treated with 1µM E2 concentrations.…”
Section: Impact On Immune Systemmentioning
confidence: 52%
“…The short exposure of Common carp macrophages to a 100 µg/L BPA concentration was followed by a significant increase in Ca 2+ levels and expression of genes such as il6, il11, M17 that are related to immunotoxicity. Similar research on the effect of 17β-ethinylestradiol on juvenile Common carp was carried out by Maciuszek et al [ 116 ]. In the in vivo part of the performed studies, fish were fed with feed with the addition of E2 (20 mg/kg) and infected with Aeromonas salmonicida bacteria, for in vitro part monocyte/macrophage cell suspensions were treated with 1µM E2 concentrations.…”
Section: Impact On Immune Systemmentioning
confidence: 52%
“…Such E2-exposure also decreased the expression of complement components ( c3-1, c3-3 and factor-H ) in the liver of Yersinia ruckeri -infected fish. In turn, our studies found that in carp fed for 14 days with an E2-containnig diet, the expression of anti-inflammatory mediators during Aeromonas salmonicida infection was higher than in fish fed with control diet (Maciuszek et al 2020a ).…”
Section: Introductionmentioning
confidence: 64%
“…For example, Cabas and co-workers (Cabas et al 2013 ) showed a decrease of phagocytosis in seabream head kidney cells treated in vitro with E2 for 1 h, while the opposite phenomenon was found in cells incubated with E2 for 16 and 48 h. Moreover, high concentrations of estradiol (10–1000 nM) reduced phagocytosis in the head kidney leukocytes of carp (Yamaguchi et al 2001 ), while a lower concentration (5.5 nM) decreased the ROS production in the head kidney cells of seabream (Chaves-Pozo et al 2003 ). In turn, in goldfish, high E2 dose (5 μM) suppressed the in vitro chemotaxis of cells from a kidney macrophage cell line (Wang and Belosevic 1995 ), while 1 μM of E2 downregulated both the expression of pro- and anti-inflammatory mediators in carp monocytes/macrophages (Maciuszek et al 2020a ). However, macrophages of seabream that were stimulated with Vibrio anguillarum genomic DNA ( Va DNA) increased their expression of pro-inflammatory mediators upon E2 treatment (18.35 or 183.55 nM) (Liarte et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in response to oestrogen exposure the complement gene expression was altered during Yersinia ruckeri infection of juvenile O. mykiss (Wenger et al ., 2011). Interestingly, feeding an oestradiol (E2)‐enriched diet increased the expression of both pro‐inflammatory and anti‐inflammatory genes in head kidney of Aeromonas salmonicida– infected C. carpio , whereas in in‐vitro experiments, E2 reduced the lipopolysaccharide (LPS)‐induced expression of pro‐ and anti‐inflammatory mediator genes (Maciuszek et al ., 2020). Thus, considering all reports, it seems that in the majority of the studies, increased levels of oestrogen are immunosuppressive (Figure 1).…”
Section: Modulation Of Immune Responses By the Reproductive Systemmentioning
confidence: 99%
“…In‐vitro studies showed that a low dose of EE2 (0.1 μM) upregulates the expression of pro‐inflammatory cytokine genes in the LPS‐stimulated macrophages isolated from the head kidney and downregulates their expression in C . carpio (Maciuszek et al ., 2020). Similar reports are found in the S .…”
Section: Modulation Of Immune Responses By Steroidogenic Edcsmentioning
confidence: 99%